UPAYA MASYARAKAT DALAM PEMANFAATAN HUTAN ADAT TIGO LUHAH DI DESA KEMANTAN KECAMATAN AIR HANGAT TIMUR KABUPATEN KERINCI - Silvia Kurnia Syahada; Ratna Wilis (JURUSAN GEOGRAFI FIS UNP, 2019)
Abstract This study aims to determine the physical and social characteristics of the Tigo Luhah Kemantan Customary Forest and to know the community's efforts in the use of the Tigo Luhah Customary Forest in the Kemantan Village, Airangat Timur District, Kerinci Regency. The research method used in this study is the combined method (Mixed Method). Research informants numbered 10 people. Data collection techniques using interviews, observation and documentation studies. The results showed that (1) physical characteristics of the Tigo Luhah Kemantan customary forest have a climate that is affected by monsoons, ultisol and podsolic soil types, the slope of the Tigo Luhah Kemantan customary forest is 15-45%. Land use is protected forest and forest production, the function of the area is a buffer zone and annual crop cultivation, (2) Utilization system in the management of the Tigo Luhah Kemantan Indigenous Forest in the form of division of 3 zones differentiated by cultivators and land type categories where there is division of farmer groups, management in the form of rules, prohibitions, customary sanctions, and wood flowers, (3) The efforts of the people of Kemantan Village to preserve forest utilization are reforestation, planting felling, selective logging and complying with applicable rules and prohibitions. Keywords : Customary forest, Efforts, Local Wisdom, Utolization